2011
DOI: 10.1007/s00421-011-1912-5
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic differences in thermoregulatory responses during resting, passive and active heating: application of Werner’s adaptation model

Abstract: For the coherent understanding of heat acclimatization in tropical natives, we compared ethnic differences between tropical and temperate natives during resting, passive and active heating conditions. Experimental protocols included: (1) a resting condition (an air temperature of 28°C with 50% RH), (2) a passive heating condition (28°C with 50% RH; leg immersion in a hot tub at a water temperature of 42°C), and (3) an active heating condition (32°C with 70% RH; a bicycle exercise). Morphologically and physical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 22 publications
(33 reference statements)
2
25
0
2
Order By: Relevance
“…All the subjects in both groups were all right-handed and had normal or corrected-to-normal visual acuity. Heat acclimatization status of the subjects in TR group was confirmed from the physiological responses during heat exposure in this study, that is they showed a smaller increase of rectal temperature ( T re ) and a small amount of total sweat rate () during heat exposure, that are commonly observed in tropical natives [18–23, 25, 26]. Therefore, subjects in TR group in this study could be considered as heat-acclimatized subjects.…”
Section: Methodssupporting
confidence: 62%
See 2 more Smart Citations
“…All the subjects in both groups were all right-handed and had normal or corrected-to-normal visual acuity. Heat acclimatization status of the subjects in TR group was confirmed from the physiological responses during heat exposure in this study, that is they showed a smaller increase of rectal temperature ( T re ) and a small amount of total sweat rate () during heat exposure, that are commonly observed in tropical natives [18–23, 25, 26]. Therefore, subjects in TR group in this study could be considered as heat-acclimatized subjects.…”
Section: Methodssupporting
confidence: 62%
“…First, we observed that subjects in tropical group showed a higher rectal temperature during control condition, a smaller increase of rectal temperature, and a less amount of total sweat rate during heat exposure than Japanese. A higher resting core temperature, a small increase of core temperature, and a less amount of total sweat rate during heat exposure are considered as the physiological adaptation feature of heat acclimatization reported in the previous studies [2123, 25]. These adaptation features to tolerate heat stress become advantages for tropical subjects in this study to deal with performance decrement during heat exposure; that is, the tropical subjects in this study could maintain mental arithmetic test performance, while it was not observed in Japanese.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…There is previous research relating to this where it has been reported that there are differences between races when it comes to human body temperature adjustment response [20,21]. For example, when exposed to heat, rectal temperatures for Malays, who live in tropical regions, do not rise as easily as the Japanese, who live in mesodermal climates, and because there is a large rise in temperature of the extremities for the Malays, they have a greater ability to effectively stabilize their internal body temperature, giving them abilities appropriate for tropical climates [22,23]. The average temperature in Japan (Fukuoka Prefecture) is 17.0 °C [24], a temperate zone, while Taipei, Taiwan has an average temperature of 23.0 °C [25], a subtropical zone, while Hanoi, Vietnam has an average temperature of 24 °C [26], a tropical zone.…”
Section: Comparison Of the Results In Japan Taiwan And Vietnammentioning
confidence: 99%
“…Heat acclimatization is triggered as a response to a variety of complex environmental factors in hot climates. Over the past half century, a number of studies on heat acclimatization have been reported in terms of physiological adaptation (Lee et al, 2011b;Saat and Tochihara, 2008;Taylor, 2006;Wakabayashi et al, 2011;. Though heat acclimatization in psycho-physiological traits has been a relatively neglected area of research, several interesting studies have been conducted.…”
Section: Introductionmentioning
confidence: 99%